The Use of Intertextuality in the Sermons of Abu Ja'far al-Mansur - Hayajneh, Mahmoud Saleem (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to elucidate the intricacies of argumentative intertextuality within the political speeches of Abu Jaafar Al-Mansur, employing it as a strategic device woven through the threads of heritage. The intersection of these threads creates countless connections by summoning diverse heritage evidence, absorbed by the preacher to unfold his speeches. The oral prose, rich in semantic nuances, draws significantly from religious texts, particularly the Qur'an and the Prophet's hadiths, forming the core of its essence. The study focuses on highlighting and manifesting these aspects through the technique of intertextuality and its associated mechanisms. Methods: The methodology involves a thorough examination of argumentative features, specifically through intertextuality, present in the political speeches of Abu Jaafar Al-Mansur. Recognizing that every creative text relies on references and sources, this study explores the rich heritage tributary forming a dialogue scene with recipients, extending beyond their conscience and feelings. Results: Results indicate that despite their brevity, these sermons exemplify argumentative excellence, incorporating mechanisms attuned to the addressees' reality, situation, and position. The research emphasizes Al-Mansur's endeavor to construct a model text endorsing his theory of the caliphate and authority, utilizing heritage texts to bolster his argumentative stance. The study concludes that intertextuality, especially of a religious nature, emerges as a highly effective mechanism, enveloping recipients intellectually and emotionally through their religious and cognitive wealth. Conclusion: This research underscores the importance of studying political speeches in the Abbasid era with an intertextual and argumentative lens to unveil their references and foundational principles.